2004
DOI: 10.1111/j.1444-2906.2004.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid class and fatty acid composition of phospholipids from the gonads of skipjack tuna

Abstract: Lipid class and fatty acid composition of phospholipids from the gonads of skipjack tuna were examined to evaluate effective utilization of the processing of by-products. The predominant phospholipids in the ovaries were phosphatidylcholine (PC; 47.9%), phosphatidylethanolamine (PE; 19.3%) and lyso-phosphatidylcholine (LPC; 19.1%). In contrast, those in the testes were PC (40.1%), PE (29.3%) and phosphatidylserine (PS; 9.6%). The percentage of docosahexaenoic acid (DHA) was markedly high at more than 50% in LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
4
17
1
1
Order By: Relevance
“…Almost all DHA levels in the PL (PE and PC) in the S. australasicus lipids exceeded 20% of TFA, similar to other fish species including tuna species (1,44,45).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Almost all DHA levels in the PL (PE and PC) in the S. australasicus lipids exceeded 20% of TFA, similar to other fish species including tuna species (1,44,45).…”
Section: Resultssupporting
confidence: 72%
“…It is well known that high levels of n-3 PUFA are generally found in the tissue PL of all marine fish species (1,44,45) because polar tissue PL work as cell membrane lipids and are generally rich in n-3 PUFA for membrane fluidity. Almost all DHA levels in the PL (PE and PC) in the S. australasicus lipids exceeded 20% of TFA, similar to other fish species including tuna species (1,44,45).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the present study also showed that, independent of dietary DHA supply, DHA in muscle tissues fluctuated during the lifecycle of Arctic charr, which suggests that DHA metabolism in Arctic charr may change with extrinsic factors, such as water temperature (Farkas et al, 1980), as well as intrinsic factors, such as gonadal development (Hiratsuka et al, 2004). This long-term study has thus provided better resolution of DHA retention in tissues over time compared to shorter feeding studies that can miss seasonal…”
Section: Discussionsupporting
confidence: 61%
“…Each band was detected under saturated iodine gas, and scraped off from the PE and PC band on the plate. The separated PE and PC were converted to fatty acid methyl ester (FAME, from diacyl type) and dimethylacetal (DMA, from plasmalogen type) by direct transesterification with methanol containing 1% concentrated hydrochloric acid for 2.5 h at 85˚C as previously described ( 18 ). The FAME and DMA were separated by gas chromatography using a flame ionization detector (GC-14A; Shimadzu Corporation, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%